Hunting the hunter - Korman, Gordon (New York : Scholastic, 2006)
When Aiden and Meg Falconer discover that Hairless Joe, a killer and madman, holds the key to freeing their parents from prison, they decide to try and trap him, despite the dangers.
"An Apple paperback."
Keywords: Fugitives from justice -- Juvenile fiction; Adventure stories; Fugitives from justice -- Fiction; Adventure and adventurers -- Fiction; Adventure fiction